Digital capital : harnessing the power of business webs - Tapscott, Don.; Lowy, Alex.; Ticoll, David (London : Nicholas Brealey, 2000)
This book is about: The new models of wealth creation; The human and relationship elements of digital capital; Strategies for business Webs; ...
Keywords: Business; Management; Data processing; Electronic commerce; Business -- Data processing; Electronic commerce